Soil degradation and crop yield declines persist 5 years after pipeline installations. Issue 2 (9th February 2023) - Brehm, Theresa; Culman, Steve
Abstract: Degradation of natural resources, including increased soil compaction, soil horizon mixing, and decreased crop yields have been common outcomes of underground pipeline installation. However, most of the research documenting the impacts of pipeline installation on soil and crops was conducted before contemporary best management practices were developed and implemented. The objective of this study was to evaluate the impact of pipeline installation on soils and field crops after a 4‐ to 5‐year remediation period, coinciding with the end of landowner compensation and when sites are considered fully remediated by pipeline companies. We report soil properties and corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] yields from three independently operated pipelines at 29 sites across 8 Ohio counties. We observed significant degradation in soil physical properties, such as surface penetration resistance (15.3% increase) and mean weight diameter of soil aggregates (13.6% decrease) in right‐of‐way (ROW) areas compared with adjacent (ADJ) areas, respectively. Soils in ROW showed evidence of soil horizon mixing, with 25.0 g kg −1 higher clay compared with ADJ areas. Soil degradation resulted in decreases of 23.8% and 19.5% in corn yields and 7.4% and 12.5% in soybean yields during 2020 and 2021, respectively. Widespread disturbance persisted 5 years following pipeline installation in soil physical, chemical, and biological properties. Current best management practices of pipeline installation and remediation employed by three companies were insufficient to combat widespread soil degradation and crop yield loss. Core Ideas: Three underground pipelines were evaluated within 5 years of installation in Ohio at 29 farms. Soil degradation persisted after the remediation period, particularly with soil physical properties. Corn yields were 23.8% and 19.5% lower over pipeline right‐of‐way (ROW) areas in 2020 and 2021, respectively. Soybean yields were 7.4% and 12.6% lower over pipeline ROW areas in 2020 and 2021, respectively. Pipeline installation and remediation best management practices were insufficient to prevent soil degradation.